Improvement of the Stability and Activity of an LPMO Through Rational Disulfide Bonds Design - Zhou, Xiaoli; Xu, Zhiqiang; Li, Yueqiu; He, Jia; Zhu, Honghui (Frontiers in Bioengineering and Biotechnology, 2022)
Lytic polysaccharide monooxygenases (LPMOs) oxidatively break down the glycosidic bonds of crystalline polysaccharides, significantly improving the saccharification efficiency of recalcitrant biomass, and have broad application prospects in industry. To meet the needs of industrial applications, enzyme engineering is needed to improve the catalytic performance of LPMOs such as enzyme activity and stability. In this study, we engineered the chitin-active CjLPMO10A from Cellvibrio japonicus through a rational disulfide bonds design. Compared with the wild-type, the variant M1 (N78C/H116C) exhibited a 3-fold increase in half-life at 60 °C, a 3.5 °C higher T5015, and a 7 °C rise in the apparent Tm. Furthermore, the resistance of M1 to chemical denaturation was significantly improved. Most importantly, the introduction of the disulfide bond improved the thermal and chemical stability of the enzyme without causing damage to catalytic activity, and M1 showed 1.5 times the specific activity of the wild-type. Our study shows that the stability and activity of LPMOs could be improved simultaneously by selecting suitable engineering sites reasonably, thereby improving the industrial adaptability of the enzymes, which is of great significance for applications.